Mental Health in Residential Healthcare Workers During the COVID-19 Pandemic: The Moderating Role of Selfobject Needs - Arble, Eamonn P.; Shankar, Sneha; Steinert, Steven W.; Daugherty, Ana M. (Frontiers in Psychiatry, 2021)
The COVID-19 outbreak has affected healthcare across all levels. Older adults and those with chronic illness are at greatest risk for infection complications and mortality, which presents significant psychological distress for residential healthcare workers. The concept of selfobject needs, consisting of Mirroring, Idealizing, and Twinship, may be relevant in explaining psychological distress. This study seeks to enhance our understanding of the needs of healthcare workers responsible for elderly patients and evaluate the role of psychosocial support through selfobject needs to mitigate the effects of trauma during the pandemic. Participants (N = 103) employed in residential healthcare facilities in the metropolitan Detroit, MI (USA) region completed an online survey during the peak initial infection. Assessments included standardized measures of trauma-related symptoms, depression, anxiety, and general distress symptoms, as well as a validated measure of selfobject needs. Residential healthcare workers reported mental health symptoms across domains, including clinical elevations in symptoms of trauma, depression and anxiety. Selfobject needs and mental health outcomes were positively correlated, indicating that greater unmet relational need was associated with greater severity of symptoms. Greater trauma symptom severity as a proxy index of current experience during the pandemic predicted high depressive symptoms, and greater Mirroring need worsened the effect. These results suggest that interventions targeting selfobject needs, specifically Mirroring, may be effective at mitigating acute mental health symptoms among healthcare workers during a distressing event.